Pharmacology of Allium sativum in relation to Cytochrome P450 and possible drug interactions - Jani, Ashutosh; Mehta, Anita (Pharmacognosy Reviews)
Allium sativum (Family Amaryllidaceae or Liliaceae) is used worldwide for various clinical uses like Hypertension, cholesterol lowering effect, antiplatelets and fibrinolytic activity etc. Due to these common house hold uses of Allium sativum as a herbal supplements, and failure of patients to inform their physician of the over-the-counter supplements they consume leads to drugnutrient interactions with components in herbal supplements. Today these type of interactions between a herbal supplement and clinically prescribed drugs are an increasing concern. In vitro studies indicated that garlic constituents modulated various CYP enzymes. CYP3A4 is abundantly present in human liver and small intestine and contributes to the metabolism of more than 50% of commonly used drugs including nifedipine, cyclosporine, erythromycin, midazolam, alprazolam, and triazolam. Extracts from fresh and aged garlic inhibited CYP 3A4 in human liver microsomes. The in vivo effects of garlic constituents are found to be species dependent and the dosing regimen of garlic constituents appeared to influence the modulation of various CYP isoforms. Studies have indicated that the inhibition of various CYPs by organosulfur compounds from garlic was related to their structure also. Studies using in vitro and in vivo animal and human models have indicated that various garlic constituents can be the substrates, inhibitors and or inducers of various CYP enzymes. The modulation of CYP enzyme activity and expression are dependent on the type and chemical structure of garlic constituents, dose regime, animal species and tissue, and source of garlic. Thus, this review throws light on the possible herb drug interaction with the use of garlic.
Keywords: Cytochrome P450; Garlic; Allium sativum; Pharmacology; Drug Interactions